2020
DOI: 10.1007/s00550-020-00507-z
|View full text |Cite
|
Sign up to set email alerts
|

Dear supplier, how sustainable are you?

Abstract: This article analyses one of the most common tools employed by global focal companies in sustainable supply chain management (SSCM) across all industries: supplier sustainability self-assessment questionnaires. Extant research has moved beyond the questions of whether and which suppliers should be assessed. Current research is already focussing on how to share and standardise such assessment data. Despite mounting general research on SSCM, we identified that specific tools such as self-assessment questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 81 publications
(103 reference statements)
0
2
0
Order By: Relevance
“…In the automotive industry, first attempts can be observed to develop and agree on sustainability assessment approaches, such as the so called "self-assessment questionnaires" (e.g., CSR Europe, 2018;Fraser et al, 2020), which cover social and environmental sustainability issues and describe standards for supplier audits and on-site assessments to assess sustainability performance of suppliers (e.g., Hannibal & Kauppi, 2018). In their study analyzing 14 industry-based initiatives, Müller and Bessas (2017) found that 12 proposed approaches to assess sustainability performance of suppliers are based on questionnaires or audits conducted by focal firms.…”
Section: Assessing Supplier Performancementioning
confidence: 99%
“…In the automotive industry, first attempts can be observed to develop and agree on sustainability assessment approaches, such as the so called "self-assessment questionnaires" (e.g., CSR Europe, 2018;Fraser et al, 2020), which cover social and environmental sustainability issues and describe standards for supplier audits and on-site assessments to assess sustainability performance of suppliers (e.g., Hannibal & Kauppi, 2018). In their study analyzing 14 industry-based initiatives, Müller and Bessas (2017) found that 12 proposed approaches to assess sustainability performance of suppliers are based on questionnaires or audits conducted by focal firms.…”
Section: Assessing Supplier Performancementioning
confidence: 99%
“…Fraser [53] analyzed supplier sustainability self-assessment questionnaires and concluded that they are one of the most-common tools used in supply chain sustainability management in almost all industries. Many industry initiatives, such as Drive Sustainability, the automotive industry peer group and its self-assessment questionnaire "Sustainability Assessment Questionnaire (SAQ)", the electronics industry citizens coalition (EICC), and the ethical toy program (IETP) in the toy industry, continue to develop common and standardized questionnaires and sustainability-related standards, in the supply chain [51][52][53][54][55][56].…”
Section: Theoretical Framework 21 Csr Requirements In the Supply Chainmentioning
confidence: 99%